Revolusi Mental Berbasis Al Qur'an: (Sebagai Penangkal Pergaulan Bebas untuk Remaja) - Khosiin, Khamam (LPPI Universitas Al-Qolam Malang, 2022)
Adolescents face various kinds of problems, which are often difficult to solve. The problems that exist among teenagers are extreme and the impact is enormous. One example of a joint PR that must be resolved immediately is the impact of adolescent promiscuity. Islam is here to provide answers to juvenile delinquency, the solution offered by Islam is to increase the worship of piety to Allah swt., to study religion and most importantly to cultivate character from an early age. Do positive activities away from negative things. So be a teenager who holds fast to religion by making the Qur'an as a guide so that teenagers will not fall into the abyss of disobedience. The effectiveness of their immediate environment, namely parents. Rasulullah saw. clearly set a good example in daily interactions. At a young age the Prophet Muhammad. has earned the nickname Al-Amin, which reflects a young man who has extraordinary character. The loss of a good role model among teenagers, causes a prolonged moral degradation. An introduction to the characteristics of the Prophet Muhammad. become absolute law to the youth of today. Key words: mental, education, adolescent, religion,